Influence of Innovative Digital Technology on Healthcare Service Performance - Hassah Obaid Ebrahiem Abdulla Alzaabi; Hazmilah Hasan (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study on innovative digital technology factors affecting UAE healthcare service practices performance. The innovative digital technology factors are clustered in four domains namely system development; IT base innovation; technology services and process integration. Data collection was conducted through questionnaire survey among healthcare employees from managers to operational workers in Dibba Hospital, Masafi Hospital, and Fujairah Hospital in UAE. The selection of respondents was carried out in two sampling approaches which are stratified sampling random sampling technique methods. A total of 300 questionnaire sets were distributed but only 281 sets of completed questionnaire were returned for the analysis. This represents the responses rate of 94%. Before conducting the ranking analysis, the collected data was characterised for its reliability and normality patterns and found that the data has achieved the reliability and normality criteria. The ranking analysis found that the most influential innovative digital technology factor is TS2 of the technology services domain. TS2 is concerning the connectivity with an extranet. The second factor is TS3 in the technology services domain which is efficient human resource management system. The third rank is SD2 system development domain which is updates the technological features of existing system to improve healthcare services. The fourth rank is BIN1 in IT base innovation domain which is adds new capabilities to the existing system. Finally, the fifth rank is BIN2 in IT base innovation domain which is new features are often added to the existing system.